Application of VACNTs in MEMS devices - MRazib, MAsyraf; Rana, M. M.; Hassan, M. A.; Saleh, Tanveer (2015)
Vertically aligned Carbon Nanotubes (CNTs) which are commonly referred to as CNT forests, have many potential engineering applications for its attractive mechanical, electrical, optical, and thermal properties. Various micro patterning of VACNTs are used for fabricating MEMS devices such as pressure sensor, thermometer, switches etc. A new patterning technique recently introduced by our group is named as micro mechanical bending (M2B) of VACNTs. Typically, CNT forest is known to be the darkest material on earth that can almost completely absorb light. This new M2B technique for CNT forest remarkably changes the optical property of the processed zone. The most significant observation made from the processed CNT forest is the visible optical reflection from bent and flattened area. Another interesting property of the resultant is anisotropic behaviour of the surface. The anisotropic and flexible nature of CNT forest has opened the gateway to use these patterned CNT forest as several types of MEMS based sensor, which will be discussed in this paper.